2013
DOI: 10.1128/ec.00334-12
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Assembly Factors CAF-1 and HIR Modulate Epigenetic Switching Frequencies in an H3K56 Acetylation-Associated Manner in Candida albicans

Abstract: CAF-1 and HIR are highly conserved histone chaperone protein complexes that function in the assembly of nucleosomes onto chromatin. CAF-1 is characterized as having replication-coupled nucleosome activity, whereas the HIR complex can assemble nucleosomes independent of replication. Histone H3K56 acetylation, controlled by the acetyltransferase Rtt109 and deacetylase Hst3, also plays a significant role in nucleosome assembly. In this study, we generated a set of deletion mutants to genetically characterize path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 69 publications
2
33
1
Order By: Relevance
“…S1 in the supplemental material). An alternative explanation supported by previous studies is that there are specific chromatin structures associated with both epigenetic transcriptional states and that mutations which impair the formation of these structures can impair the stability of one or both states (50,52). Previous studies of the med16⌬ mutation in S. cerevisiae support the idea that Med16 could impact the stability of chromatin structures and epigenetic states (22,26), although the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…S1 in the supplemental material). An alternative explanation supported by previous studies is that there are specific chromatin structures associated with both epigenetic transcriptional states and that mutations which impair the formation of these structures can impair the stability of one or both states (50,52). Previous studies of the med16⌬ mutation in S. cerevisiae support the idea that Med16 could impact the stability of chromatin structures and epigenetic states (22,26), although the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 49%
“…The only other two mutations found to have a similar impact are deletion of CAC2, which is part of the CAF-1 complex that functions mainly in replicationcoupled nucleosome assembly (52), and deletion of RPD3, a histone deacetylase associated with transcriptional repression (49). With the exception of the increased EFG1 expression in med16⌬/⌬ opaque cells, there appear to be no significant changes in the expression levels of the key components of the Wor1 circuit (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the swr1 mutant showed no increased growth sensitivity to hydroxyurea or heat and osmotic stress (not shown). We have previously shown that the rtt109 mutant has an increased rate of generating aneuploidy (25). However, we did not observe any increase in aneuploidy formation in the swr1 mutant after growth on L-sorbose medium (not shown).…”
Section: Resultscontrasting
confidence: 41%
“…Treatment with nicotinamide (NAM), which can inhibit sirtuin activity noncompetitively (22,23) and increases H3K56ac levels, also promotes switching to the opaque form, and this activity has also been shown to be dependent on RTT109 (24). Furthermore, hyperacetylation of H3K56 is toxic to C. albicans (21,25).…”
mentioning
confidence: 99%